PENGEMBANGAN URBAN FARMING MENUJU KETAHANAN PANGAN KELUARGA - Fawwaz, Muhammad Iqbal; Akbar, Muhammad Fikri; Churiyah, Madziatul; Sholikhan (Transpublika Publisher, 2022)
In Mergosono Village, the program for using terraces to grow crops was carried out more than 5 years ago, through an “urban farming” program led by PKK women. There were more than 50 mothers who were involved in this activity. Through urban farming, each house is recommended to plant more than 10 potted plants, with various kinds of plants, such as: chilies, tomatoes, cabbage, eggplant, pok cay, mustard greens, and flowers. At first this activity only aimed to maintain the beauty of the village, so that it remains beautiful, but gradually it can be used to meet daily food needs, especially vegetables and